1994
DOI: 10.1116/1.578927
|View full text |Cite
|
Sign up to set email alerts
|

Unique hydride chemistry on silicon–PH3 interaction with Si(100)-(2×1)

Abstract: The dissociative adsorption of phosphine (PH3) on Si(100)-(2×1) and its high temperature thermal behavior have been studied by high-resolution electron energy loss spectroscopy (HREELS), Auger electron spectroscopy, and by temperature programmed desorption (TPD). Phosphine adsorbs dissociatively onto Si(100)-(2×1) at 100 K as PH2 and H species, as revealed by vibrational bands at 1050 cm−1 [δsc(PH2)] and 2100 cm−1 [ν(Si–H)]. The PH2(a) undergoes thermal decomposition to adsorbed P and H near 650 K, as determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
9
22
0
Order By: Relevance
“…III B and III C. PH 3 dissociatively adsorbs on Si͑001͒ as PH 2 and H at 100 K, with the onset of PH 2 decomposition occurring at T s Ͼ 225°C. 13 Thus, in our dosing experiments at T s = 300-400°C, PH 3 decomposes into adsorbed P and three H. Since the H 2 desorption rate at these temperatures is negligible, P ϳ 0.25 ML. AES measurements show that P remains constant with increasing T s until the onset of hydrogen desorption at ϳ400°C, above which P increases, reaching a maximum at ϳ550°C, and then decreases at T s Ͼ 600°C.…”
Section: A P-adsorbed Si"001… Samplesmentioning
confidence: 77%
See 1 more Smart Citation
“…III B and III C. PH 3 dissociatively adsorbs on Si͑001͒ as PH 2 and H at 100 K, with the onset of PH 2 decomposition occurring at T s Ͼ 225°C. 13 Thus, in our dosing experiments at T s = 300-400°C, PH 3 decomposes into adsorbed P and three H. Since the H 2 desorption rate at these temperatures is negligible, P ϳ 0.25 ML. AES measurements show that P remains constant with increasing T s until the onset of hydrogen desorption at ϳ400°C, above which P increases, reaching a maximum at ϳ550°C, and then decreases at T s Ͼ 600°C.…”
Section: A P-adsorbed Si"001… Samplesmentioning
confidence: 77%
“…PH 3 has been shown by high-resolution electron energy loss spectroscopy ͑HREELS͒ to dissociatively adsorb on Si͑001͒ as PH 2 and H at 100 K, while the onset of PH 2 dissociation to adsorbed P and two H adatoms occurs at T s Ͼ 225°C. 13 The overall PH 3 adsorption reaction can, therefore, be expressed as PH 3 ͑g͒ → PH 2 ͑ad͒ + H͑ad͒ → P͑ad͒ + 3H͑ad͒. ͑8͒…”
Section: A Ph 3 Adsorption On Si"001…mentioning
confidence: 99%
“…Phosphine (PH 3 ) is a common source of phosphorus in the chemical vapor deposition of n-type silicon for the semiconductor industry [1]. The dissociation chemistry of PH 3 on the silicon (001) surface is therefore of considerable technological relevance and has been the subject of numerous experimental [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and theoretical studies [16][17][18][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the lower coverage P 2 desorption peaks presented by Jacobson et al 27 and Hirose and Sakamoto, 28 the approximate activation energy relevant to this work falls within the range 2.6-3.5 eV. We note in passing that Yu et al 3 used n-type substrates while Colaianni et al 6 used p-type substrates; the similarity between the activation energies in Table I indicates that substrate doping and surface band bending do not affect the reaction energetics.…”
Section: Introductionmentioning
confidence: 91%
“…A summary of the relevant results is given in Table I. Yu et al 3 observed P 2 desorption over a broad temperature range with a maximum at 1000 K while Colaianni et al 6 used a slower heating rate of 2 K/s and observe a maximum at 945 K. Jacobson et al 27 showed that P 2 desorption is dependent on phosphorus coverage: at low coverage the peak desorption occurs at 1090 K while at higher coverage additional peaks are observed at approximately 800 and 950 K. Hirose and Sakamoto 28 performed a similar study and report peak temperatures ranging from 1050 to 1300 K with the peak desorption at low coverage occurring at approximately 1150 K. In Table I we translate these various peak temperatures into approximate activation energies ͑E A ͒. In this work we will focus on the low coverage limit, since higher coverages are complicated by the close proximity of many nearby phosphorus atoms.…”
Section: Introductionmentioning
confidence: 96%